Formation of Student Character Through School Culture At Sawang Elementary School, North Aceh Regency - Fauzah, Fauzah; Fitrah, Hariki; Syahrin, Alfi (Postgraduate School, Universitas Negeri Padang, 2023)
character values contained in religious culture. This type of research is descriptive using a qualitative approach. The research location was Elementary School (ES) 26 Sawang, North Aceh Regency. The research subjects are school principals, teachers, and students. Data collection techniques through observation, interviews, and documentation. Technique the validity of the data using triangulation techniques. Data analysis using data reduction, data display, and conclusion. The research results show that 1) the formation of student character through religious culture is carried out through praying before and after learning, reading Yasin every Friday, reading Asmaul Husna every Thursday, and dhikr activity every Friday; and 2) The meaning of this religious culture is the formation of religious and moral student character glorious. The religious culture developed at ES 26 Sawang has character values such as the values of faith and piety, Akhlakul qarimah, discipline, responsibility, mutual respect, and cultur smiles, greetings, greetings, politeness.